Intrahippocampal injection of IL‐1β upregulates Siah1‐mediated degradation of synaptophysin by activation of the ERK signaling in male rat. Issue 6 (31st January 2023) - Zhou, Qiuping; Lin, Lanfen; Li, Haiyan; Li, Yichen; Liu, Nan; Wang, Huifang; Jiang, Shuqi; Li, Qian; Chen, Zhuo; Lin, Yiyan; Jin, Hui; Deng, Yiyu
Abstract: Interleukin‐1β (IL‐1β) has been described to exert important effect on synapses in the brain. Here, we explored if the synapses in the hippocampus would be adversely affected following intracerebral IL‐1β injection and, if so, to clarify the underlying molecular mechanisms. Adult male Sprague–Dawley rats were divided into control, IL‐1β, IL‐1β + PD98059, and IL‐1β + MG132 groups and then sacrificed for detection of synaptophysin (syn) protein level, synaptosome glutamate release, and synapse ultrastructure by western blotting, glutamate kit and electron microscopy, respectively. These rats were tested by Morris water maze for learning and memory ability. It was determined by western blotting whether IL‐1β exerted the effect of on syn and siah1 expression in primary neurons via extracellular regulated protein kinases (ERK) signaling pathway. Intrahippocampal injection of IL‐1β in male rats and sacrificed at 8d resulted in a significant decrease in syn protein, damage of synapse structure, and abnormal release of neurotransmitters glutamate. ERK inhibitor and proteosome inhibitor treatment reversed the above changes induced by IL‐1β both in vivo and in vitro. In primary cultured neurons incubated with IL‐1β, the expression level of synaptophysin was significantly downregulated coupled with abnormal glutamate release. Furthermore, use of PD98059 had confirmed that ERK signaling pathway was implicated in synaptic disorders caused by IL‐1β treatment. The present results suggest that exogenous IL‐1β can suppress syn protein level and glutamate release. A possible mechanism for this is that IL‐1β induces syn degradation that is regulated by the E3 ligase siah1 via the ERK signaling pathway. Abstract : A schematic diagram depicting a pre‐synaptic mechanism in this study. The present study has provided experimental evidence demonstrating that exogenous IL‐1β injection could lead to the activation of microglia and astrocyte and release some endogenous IL‐1β. The exogenous and endogenous IL‐1β can cause the degradation of syn and suppress glutamate release through IL‐1 receptor in the hippocampus. A possible mechanism for this is that syn degradation is mainly regulated by the E3 ligase siah1 via the ERK signaling pathway. The downregulation of syn is positively related to the decreased release of glutamic acid.